Answer:
The graph in the attached figure
Step-by-step explanation:
we know that
The equation of a line in point slope form is
![y-y1=m(x-x1)](https://tex.z-dn.net/?f=y-y1%3Dm%28x-x1%29)
we have
![(x_1,y_1)=(6,3)](https://tex.z-dn.net/?f=%28x_1%2Cy_1%29%3D%286%2C3%29)
![m=\frac{1}{4}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B1%7D%7B4%7D)
substitute
![y-3=\frac{1}{4}(x-6)](https://tex.z-dn.net/?f=y-3%3D%5Cfrac%7B1%7D%7B4%7D%28x-6%29)
The easiest way to graph a line is to calculate the intercepts
The<u><em> x-intercept </em></u>is the value of x when the value of y is equal to zero
For y=0
![0-3=\frac{1}{4}(x-6)](https://tex.z-dn.net/?f=0-3%3D%5Cfrac%7B1%7D%7B4%7D%28x-6%29)
![-12=(x-6)](https://tex.z-dn.net/?f=-12%3D%28x-6%29)
![x=-12+6=-6](https://tex.z-dn.net/?f=x%3D-12%2B6%3D-6)
The x-intercept is the point (-6,0)
The <u><em>y-intercept</em></u> is the value of y when the value of x is equal to zero
For x=0
![y-3=\frac{1}{4}(0-6)](https://tex.z-dn.net/?f=y-3%3D%5Cfrac%7B1%7D%7B4%7D%280-6%29)
![y-3=-\frac{3}{2}](https://tex.z-dn.net/?f=y-3%3D-%5Cfrac%7B3%7D%7B2%7D)
![y=-\frac{3}{2}+3](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B3%7D%7B2%7D%2B3)
![y=1.5](https://tex.z-dn.net/?f=y%3D1.5)
The y-intercept is the point (0,1.5)
Plot the intercepts and join the points to graph the line
(-6,0) and (0,1.5)
The graph in the attached figure